Guidelines for management of ischaemic stroke and transient ischaemic attack 2008 - Ringleb, Peter A.; Bousser, Marie-Germaine; Ford, Gary; Bath, Philip M.W.; Brainin, Michael; Caso, Valeria; Cervara, Álvaro; Chamorro, Angel; Walker, Marion F. (Karger Publishers, 2008)
This article represents the update of the European Stroke Initiative Recommendations for Stroke Management. These guidelines cover both ischaemic stroke and transient ischaemic attacks, which are now considered to be a single entity. The article covers referral and emergency management, Stroke Unit service, diagnostics, primary and secondary prevention, general stroke treatment, specific treatment including acute management, management of complications, and rehabilitation.